The Cultural Heritage of Western Rajasthan: Need for Preservation - Rathore, G. S. (National Geographical Journal of India, 2022)
he human culture, survived and flourished through the span of time with its vivid aspects such as history, philosophy, literature, folklore and music, paintings, craft works, fairs and festivals, customs and traditions is undoubtedly unique. However, with the advent of modern science and technological era, its deep rooted cultural heritage has been badly shaken. Thus, there is a need to preserve and revive the rich cultural heritage of the region so that the posterity may not be deprived of this invaluable "treasure’. The objective of this paper is to delineate and interpret the main characteristic/aspect of the cultural heritage of Western Rajasthan and suggest some of the suitable measure which may be helpful in the revival and the preservation of this excellent or good cultural characteristics or the achievements, works, expressions, traditions etc which we have got through our predecessors or by past time.